Proactive Participation: Assesing Village Community Involvement in Stunting Prevention Program (Case Study: Tonasa Village) - Ismail, Nuralamsyah; Zhafran Fadli, A.M.Rafi; Nasution, Adnan; Ahmad Yani, Andi; Lambali, Suryadi (Indonesian Association for Public Administration (IAPA), 2023)
Participation is an effort that must continue to be encouraged, in addition to focusing on the democratic right to be involved in the public policy process, it also focuses on the effectiveness of policy delivery. Participation can be contextualized in various problems that occur in society, one of which is the issue of stunting. A problem that attacks toddlers and certainly has an impact on future generations in Indonesia. Therefore, this research focuses on the participation efforts made in the planning and implementation process of the Stunting Program in Tonasa Village, Takalar Regency, which is expected to contribute knowledge related to this issue. This location was chosen because it is one of the villages that has a high percentage of stunting prevalence. This research uses a Qualitative approach with a case study model. First, the participant selection indicator in the planning stage is at the professional stakeholder level, while the implementation stage shows that the level of participation is at the open recruitment targeted level. Second, the communication and decision indicator in the program planning stage shows that the level of participation is at the level of express preferences, then in the program implementation stage shows that the level of participation is at the level of listen as spectator. Third, the authority and power indicator in the program planning stage shows that the level of community participation is at the advice and consult level, while the implementation stage shows that the level of participation is at the co-governance level.